Principles of Accounting/Introduction to Accounting. - Lammers, Lucille E.; Dominiak, Gere (The Accounting Review, 1977)
Reviews two books on accounting. "Principles of Accounting" and "Introduction to Accounting," by Richard W. Metcalf and Pierre L. Titard.